2020
DOI: 10.1007/s00262-020-02804-4
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and MEK inhibition in melanoma patients enables reprogramming of tumor infiltrating lymphocytes

Abstract: Background Combined inhibition of BRAF/MEK is an established therapy for melanoma. In addition to its canonical mode of action, effects of BRAF/MEK inhibitors on antitumor immune responses are emerging. Thus, we investigated the effect of these on adaptive immune responses. Patients, methods and results Sequential tumor biopsies obtained before and during BRAF/MEK inhibitor treatment of four (n = 4) melanoma patients were analyzed. Multiplexed immunofluorescence staining of tumor tissue revealed an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Improved antigenspecific T cell function has been associated with antigen clearance in humans with hepatitis C infection treated with direct-acting antiviral therapies (62)(63)(64)(65)(66). Similarly, an immunomodulatory effect of dasatinib on T cells has been associated with improved antitumor immunity (67,68), and BRAF and MEK inhibition in patients with melanoma leads to up-regulation of TCF7 and expansion of melanoma-specific tumor-infiltrating lymphocyte (TIL) (69). Collectively, these observations suggest that the transient cessation of TCR signaling could provide a widely applicable but underappreciated approach to enhance functionality in populations of exhausted human T cells; however, additional studies are needed to more fully define the effects of rest on nonengineered, exhausted T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Improved antigenspecific T cell function has been associated with antigen clearance in humans with hepatitis C infection treated with direct-acting antiviral therapies (62)(63)(64)(65)(66). Similarly, an immunomodulatory effect of dasatinib on T cells has been associated with improved antitumor immunity (67,68), and BRAF and MEK inhibition in patients with melanoma leads to up-regulation of TCF7 and expansion of melanoma-specific tumor-infiltrating lymphocyte (TIL) (69). Collectively, these observations suggest that the transient cessation of TCR signaling could provide a widely applicable but underappreciated approach to enhance functionality in populations of exhausted human T cells; however, additional studies are needed to more fully define the effects of rest on nonengineered, exhausted T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical response of BRAF inhibitors is usually short-lived [ 108 ], and as the disease progresses, alternative treatments available to patients is limited. Peiffer and colleagues indicated that BRAF/MEK inhibitors can promote the proliferation of melanoma-specific T cells in patients with melanoma [ 109 ]. Recently, in a clinical trial, seven of 11 patients with metastatic melanoma who received a combination treatment of TILs, HD IL-2, and vemurafenib experienced an objective clinical response, two of which achieved a complete response [ 110 ].…”
Section: Combination Therapy With Tilsmentioning
confidence: 99%
“…These are essential for central memory and maintenance of more differentiated T cells, respectively. An analysis conducted in melanoma patients showed that T-bet and TCF7 are upregulated by BRAF/MEK inhibition [ 34 ]. The repertoire of T cells found in tumors before treatment is expanded after the administration of BRAF/MEK inhibitors.…”
Section: T Cells and Their Repertoiresmentioning
confidence: 99%
“…T-bet is important to maintain the balance between T cell memory and effector differentiation pathways and to trigger Th1 responses characterized by the interferon gamma (IFN-γ) signature [ 36 ]. These findings suggest that TCF7 and T-bet induced during BRAF/MEK inhibition promote the repertoire expansion of intratumoral T cells [ 34 ].…”
Section: T Cells and Their Repertoiresmentioning
confidence: 99%